Pengajian Berbasis TPQ (Taman Pendidikan Al-Quran) bagi Pendidikan Anak untuk Meningkatkan Potensi Desa Gambiran - Aisa, Aufia; Anam, Moh Khoirul; Hidayah, Nurul; Al-Ghozali, M.Dzikrul Hakim; Veri, Achmad Riyan; Rozaki, M Iftakhur; Adawiyah, Robiatul; Andani, Dita Dwi Cahya Andani (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
One of the efforts to increase the understanding of the people of Gambiran Village from a religious perspective is that the service program is holding a